Pea, Pigeon—Cajanus cajan (L.) Millsp. - James M. Stephens (EDIS)
This document provides an overview of the pigeon pea (Cajanus cajan), a legume cultivated primarily in tropical regions for its edible seeds and pods. It describes the plant’s characteristics, including its adaptability to semiarid conditions, and outlines cultivation practices such as planting rates and seasonal timing. Although not widely grown in the continental U.S., pigeon pea has various uses including food, fodder, green manure, and as a cash crop. The document also highlights its potential yield and resilience, making it a valuable crop in suitable climates. Original publication date May 1994.